PULMONARY ARTERIAL HYPERTENSION DIAGNOSTICS SPECIFICS IN SYSTEMIC SCLERODERMIA - M. A. Simakova; A. L. Maslyansky; A. V. Naymushin; N. A. Klyaus; O. M. Moiseeva (Российский кардиологический журнал)
Aim. Pulmonary arterial hypertension (PAH) in systemic sclerodermia patients (SSD) is associated with poorer outcomes. Aim of current study is to assess the prevalence of PAH associated with SSD, among patients with newly diagnosed pulmonary hypertension (PH), included to the registry of Federal Almazov North- West Medical Research Centre and to conduct the analysis of applicability of the algorithms for earlier diagnostics of PH in SSD patients.Material and methods. To comparative analysis we included patients with idiopathic PAH (iPAH) and PAH associated with SSD (SSD-PAH). All patients underwent thorough echocardiographic test (EchoCG), 6-minute walking test (6WT), spirometry. To confirm the diagnosis of PAH we applied the right chambers catheterization (RCC).Results. Totally, 33 SSD patients included complaining on dyspnea, of those 14 had verified PAH and were taking specific treatment. With PHAROS algorithm we were able to separate additional risk subgroup of 6 patients for further study. Among participants, iPAH had 44%, and SSD-PAH — 11%. Most patients in both groups had III-IV FC (WHO) of PH: 55% of iPAH and 75% of PAH-SSD. In SSD patients there were lower values of the right ventricle systolic function by EchoCG [FAC=26±7% (р=0,028); TAPSE=15±3 mm (р=0,027); TAS’V=9±2 cm/s (р=0,023)]; values of lung diffusion capacity (DLco): 46±14% vs 62±16% in iPAH group (р=0,001) and distance of 6WT: 326±105 m vs 383±106 m (р=0,041). This data correlates with foreign registers and witness serious prognosis in PAH-SSD.Conclusion. Our study demonstrated significance of novel algorithms development for earlier diagnostics of PAH and start of specific treatment according to severity of prognosis of SSD-PAH patients. Current guidelines for PAH diagnostics use DETECT algorithm as recommended for application in patients with SSD lasting for more than 3 years and DLco below 60%. We demonstrated the worth of inclusion in investigation algorithm for SSD the additional echocardiographic criteria for PH to increase specificity.